Mechanisms and therapeutic strategies linking mesenchymal stem cells senescence to osteoporosis - Tong, Yashuang; Tu, Yulin; Wang, Jingying; Liu, Xiuyu; Su, Qian; Wang, Yanghao; Wang, Weizhou (Frontiers in Endocrinology, 2025)
Osteoporosis is a common age-related bone metabolic disorder that significantly affects skeletal health, especially in aging populations. With global demographic shifts, the rising prevalence and disability burden of osteoporosis has placed increasing pressure on healthcare systems, making it a key area of research. A crucial factor in osteoporotic progression is the aging of mesenchymal stem cells (MSCs), which weakens bone regeneration through multiple mechanisms, including reduced osteogenic differentiation, heightened oxidative stress, chronic inflammation, and disrupted bone homeostasis. This review explores the intricate relationship between MSCs aging and osteoporosis development, focusing on key processes such as cell cycle arrest, telomere shortening, epigenetic changes, and osteogenic marker expression dysregulation. We also examine potential therapeutic strategies aimed at alleviating MSCs aging, including stem cell-based treatments, senolytic agents, inhibitors targeting the senescence-associated secretory phenotype, and biomaterial-assisted approaches such as extracellular vesicles and stimuli-responsive hydrogels. This review aims to provide insights into developing precise therapeutic strategies to restore MSCs function and slow bone loss. Furthermore, we discuss interdisciplinary approaches that link molecular mechanisms to practical applications, offering a broader perspective on addressing osteoporosis in aging societies.